2015
DOI: 10.1016/s2095-3119(15)61093-0
|View full text |Cite
|
Sign up to set email alerts
|

Climate change adaptation, greenhouse gas mitigation and economic profitability of conservation agriculture: Some examples from cereal systems of Indo-Gangetic Plains

Abstract: Achieving sustainability of the cereal system in the Indo-Gangetic Plains (IGP) of India under progressive climate change and variability necessitates adoption of practices and technologies that increase food production, adaptation and mitigation in a sustainable way. This paper examines CA from the perspective of: (i) increased yield and farm income, (ii) adaptation to heat and water stresses, and (iii) reduction in greenhouse gas (GHG) emissions. The analyses and conclusions are based on the literature and e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
88
0
3

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 136 publications
(91 citation statements)
references
References 29 publications
0
88
0
3
Order By: Relevance
“…Similarly, CD can help adapt them to crop pest and disease that may increase due to high temperature (Lin, ). Minimum tillage (MT) can help them to escape the terminal heat in the case of wheat crop by facilitating early establishment (Sapkota et al ., ). Farmers who faced decreasing rainfall as a major climate risk are more likely to adopt STV and LLL.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Similarly, CD can help adapt them to crop pest and disease that may increase due to high temperature (Lin, ). Minimum tillage (MT) can help them to escape the terminal heat in the case of wheat crop by facilitating early establishment (Sapkota et al ., ). Farmers who faced decreasing rainfall as a major climate risk are more likely to adopt STV and LLL.…”
Section: Resultsmentioning
confidence: 97%
“…This study focuses on five CSA practices that are among the key practices promoted by the CGIAR Research Program on Climate Change, Agriculture and Food Security (CRP CCAFS) in south Asia. These CSA practices are found to have clear economic as well as climate change adaptation and/or mitigation benefits (for example, see Aryal et al ., , ; Erenstein et al ., ; Khatri‐Chhetri et al ., ; Sapkota et al ., ). According to CCAFS, CSA refers to those practices that help climate change adaptation, GHG mitigation and food security (for details see Aggarwal et al ., ; http://www.ccafs.cgiar.org).…”
Section: Introductionmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have shown that diversification and adoption of conservation practices have significantly improved soil quality and agricultural sustainability in the region (Ghimire et al 2016;Sapkota et al 2015;Schwab, Schickhoff, and Fischer 2015). However, more research will clarify how different soil quality and agricultural sustainability indicators respond to alternative agricultural systems.…”
Section: Resultsmentioning
confidence: 99%
“…Similarly, Sapkota et al (2015), among other authors, support conservation farming that is attentive to the soil, profitable and sustainable, protecting the environment, supporting sustainability. Conde (2014) proposed the eco-friendly farming that reduces ecological impact and intelligent farming that seeks sustainable increase of production and income, greater resilience, adaptation and mitigation.…”
Section: Sustainable Adaptation Strategiesmentioning
confidence: 88%